The Relationship Between Exclusive Breastfeeding and Speech Delay in Toddlers in Coastal Areas - Ellyani Abadi; Haswindah Arifin; Siti Hadrayanti Ananda (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Speech delay in early childhood is a serious problem that affects communication and cognitive development. Exclusive breastfeeding may be related to children’s speech development. The purpose of this study was to determine the relationship between exclusive breastfeeding and speech delay in toddlers in the coastal area of the Lansilowo Community Health Center. This was a quantitative, cross-sectional study. The sample consisted of 62 toddlers aged 24-59 months in the working area of the Lansilowo Health Center in Konawe Kepulauan Regency in June 23-September 9, 2025. The sampling technique used was proportionate stratified random sampling. Data on speech delay were assessed using the Denver II instrument, which is a validated and reliable questionnaire, and analyzed using Fisher’s exact test. The results showed that of the 2 toddlers who were exclusively breastfed, 100% did not have speech delays. Furthermore, of the 60 toddlers who were not exclusively breastfed, the majority had speech delays (93.3%). The Fisher’s exact test yielded a p-value of 0.008. The study concludes that an exclusive breastfeeding history was associated with speech delay among toddlers, and there is a relationship between exclusive breastfeeding and speech delay in toddlers Keywords: Child Development, Coastal Areas, Exclusive Breastfeeding, Speech Delay, Toddlers